Analysis of cerebrospinal fluid for xanthochromia versus modern computed tomography scanners in the diagnosis of subarachnoid haemorrhage: experience at a tertiary trauma referral centre. (January 2016) - Goyale, A; O'Shea, J; Marsden, J; Keep, J; Vincent, RP
Background: Diagnosis of subarachnoid haemorrhage, a neurosurgical emergency in patients with headache remains a logistical challenge. The rationale of the traditional pathway of cerebrospinal fluid xanthochromia analysis following negative computed tomography head scans to exclude subarachnoid haemorrhage has been challenged by the increasing accuracy of modern computed tomography scanners. Aim: We set out to establish whether our xanthochromia service was adding value to the diagnostic pathway for subarachnoid haemorrhage or whether it was acting merely as a supportive test. Method: A retrospective audit of all cerebrospinal fluid requests received since the inception of Xanthochromia service at a tertiary trauma centre. Cases interpreted as being consistent with subarachnoid haemorrhage based on cerebrospinal fluid xanthochromia analysis were selected for in-depth review from the total number of cases. Results: In total 660 requests were received for cerebrospinal fluid xanthochromia between August 2009 and July 2012. A total 28 of these were interpreted as being consistent with subarachnoid haemorrhage. Only 18 (64.3%) of requests were deemed appropriate as the clinical presentation in the remaining 10 (35.7%) was strongly suggestive of other causes of headache. A final clinical diagnosis of subarachnoid haemorrhage was made in 11 of the 18 patients who had cerebrospinal fluid xanthochromia requested appropriately. From these 11, five (45%) were deemed initially computed tomography negative and cerebrospinal fluid analysis led to final correct diagnosis of subarachnoid haemorrhage and appropriate surgical management. Conclusion: Despite improved computed tomography scanning technology, cerebrospinal fluid xanthochromia interpretation aids in the definitive diagnosis of subarachnoid haemorrhage. When requested appropriately cerebrospinal fluid xanthochromia analysis remains a vital service as results impact on clinical decision making, especially when computed tomography scan results are equivocal and is also important in later presenting patients when computed tomography accuracy decreases.